Khotmil Quran and Writing It Down to Provide an Understanding of Islam: Khotmil Qur’an Dan Membumikannya Dalam Memberikan Pemahaman Agama Islam - Matmudi; M. Yusron Maulana El-Yunusi; Nelud Daraajatul Aliyah (Universitas Darunnajah, Jakarta, Indonesia, 2025)
The environment is an important part of human life, which needs to be maintained to create harmony between humans and nature. Students of Sunan Giri University Surabaya (UNSURI) carried out community service activities in Joyoboyo Wonokromo Village, Surabaya with a focus on grounding and providing an understanding of Islam that is often ignored by the surrounding community. The activity which is carried out once a month includes the Qur'an Khotmil and continues with an understanding of the Tafsir Al-Qur'an which is followed by local residents and the youth of the Husnul Khotimah mosque. This program uses an Asset Based Community Development (ABCD) approach which emphasizes utilizing the assets and potential of the community in Joyoboyo village, Sawunggaling subdistrict, Wonokromo subdistrict, Surabaya city. then gather into a community to become a social justice advocacy platform. So that the potential of the community can be utilized optimally, the ABCD technique is very appropriate to be applied in Wonokromo District. where the religious traditions of the people of Joyoboyo village, Sawunggaling subdistrict, Wonokromo subdistrict, Surabaya city are practiced. The large presence of TPQ and Madin shows that Joyoboyo village, Sawunggaling sub-district, Wonokromo sub-district, Surabaya city has a very religious feel, the series of events include the following Al-Qur'an sermon by the people who attended. Then it closed with a study of the interpretation of the Al-Qur'an plus prayer. The results of the activity show the enthusiasm of residents in practicing the Islamic religious knowledge that has been conveyed so that it can be applied in everyday life. Through active participation, this activity not only improves the quality of local residents, but also improves spiritual and social values ​​in Joyoboyo Village, Wonokromo Surabaya.Keywords: Khotmil Al-Qur'an, Religious Understanding, Society, Mosque Youth